Management of Traumatically Intruded Permanent Incisors during an Ongoing Orthodontic Treatment - Varuni Iyer; Harshavardhan Kidiyoor; Roopak D. Naik (Contemporary Clinical Dentistry)
Intrusive luxation is one of the most severe types of dental trauma that needs immediate intervention. Various treatment modalities are passive, active, and surgical repositioning performed to prevent healing complications such as root resorption, pulp necrosis, ankylosis, and infraocclusion of the traumatized teeth. This case report discusses a patient with traumatically intruded incisors while undergoing orthodontic treatment. Active repositioning, namely orthodontic traction using light and continuous forces were directed onto the intruded teeth commenced 1 month post the injury and brought into occlusion. Clinical and radiographic evidence for the pulpal and periodontal evaluation were done after a year of active treatment. Thus, it can be concluded that observation for a span of 6–12 months before treatment is not necessary to be advocated and immediate intervention is advisable.